Mobile Service Provider In Malaysia: A Case Study Of Maxis Communication Berhad - Jacob, Marilyn (2008)
Situational analysis will be done on general external environment and the mobile service provider industry in particular through techniques such as Competitor Profile Matrix (CPM).